2007
DOI: 10.1017/s0144686x07006009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding financial elder abuse in families: the potential of routine activities theory

Abstract: The aim of this paper is to stimulate theoretical thought about financial elder abuse within families, by exploring the potential of ' routine activities theory' for raising our understanding of, and response to, its occurrences. Research into financial elder abuse, defined as the illegal or improper use of a person's finances or property by another person, has tended to emphasise the abusive event and the associated risk factors. 'Routine activities theory ', in contrast, directs attention more to developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…In Australia, research by Setterlund et al (2007) investigated the management of family finances from the perspective of 'routine activities theory'. This theory sets family involvement in finances as a caring responsibility, suggesting financial abuse is at the extreme end of likely occurrences.…”
Section: Definitions and Prevalencementioning
confidence: 99%
“…In Australia, research by Setterlund et al (2007) investigated the management of family finances from the perspective of 'routine activities theory'. This theory sets family involvement in finances as a caring responsibility, suggesting financial abuse is at the extreme end of likely occurrences.…”
Section: Definitions and Prevalencementioning
confidence: 99%
“…Material and financial abuse has been very well documented. This can be explained by the fact that it surfaced as the second most widespread form of abuse in several studies (the first place being occupied by neglect or psychological abuse; see Biggs et al 2009;Setterlund et al 2007;Rabiner et al 2004). Only one case out of 25 would be reported (National Center on Elder Abuse 2005).…”
Section: Property Crimes Selectively Targeted At the Very Old: A Casementioning
confidence: 90%
“…Payne and Fletcher (2005) and Payne andGainey (2006, 2007) also have taken a routine activities perspective on abuse in institutional care. Payne (2006) and Setterlund et al (2007) have applied RAT concepts to financial elder abuse, Dietz and Wright (2005) to the topic of victimization of older homeless people. These studies assume that elder abuse may well be regarded as intentional and goal-oriented behaviour.…”
Section: Routine Activity Theorymentioning
confidence: 99%
“…Recent definitional debates highlight the importance of trust: "Being attacked or robbed by a stranger or an acquaintance is assault or theft but not physical or financial abuse. Other studies observed that relatives of people with dementia may not intend to abuse but may be confused when managing other people's money (Langan and Means, 1996;Baxter et al, 2008) or hold "distorting'' views about their "entitlement'' to these assets (Tilse et al, 2005;Setterlund et al, 2007). Other studies observed that relatives of people with dementia may not intend to abuse but may be confused when managing other people's money (Langan and Means, 1996;Baxter et al, 2008) or hold "distorting'' views about their "entitlement'' to these assets (Tilse et al, 2005;Setterlund et al, 2007).…”
Section: Introductionmentioning
confidence: 99%